Kan grannar dela solel? En studie av lokal eldelning i svenska småhusområden - Evaldsson,Hanna; Bhattacharyya,Maya (2026)
This master thesis investigates the potential and limitations of local electricity sharing in residential distribution networks by analysing the correlation between local photovoltaic (PV) generation and electricity consumption in existing rural low-voltage grids. The study is based on quarter-hour resolution measurement data from 2025 provided by E.ON, including consumption and production data from individual households and five substations. The objective was to evaluate how local PV generation affects substation power profiles, to what extent PV production coincides with neighbouring households’ electricity demand, and what the potential for electricity sharing is in Sweden as well as what hinders it at the moment. A quantitative methodology was applied on both system and household level, including simulated scenarios with battery energy storage. The results show limited overall impact on substation power profiles but clear seasonal variations in coincidence between production and consumption. The aggregation factor varies from around 0-10% during the winter to up to 50% during the summer. Battery storage improves self-consumption and local electricity sharing potential. The results also show that electricity sharing already occurs physically in today’s electricity grid, but that economic and regulatory structures to enable virtual sharing between households within existing grid infrastructure are still lacking.
Keywords: Energigemenskaper; lokal eldelning; sammanlagring; energilagring; batterier; lågspänningsnät; småhus; solproduktion; virtuell delning